Principal's Communication Style and its Impact on the Performance of State Civil Apparatus - Otto Sariani Talaumbauna; Erman Anom; Iswadi Iswadi (Program Studi Manajemen Pendidikan Islam Institut Pesantren KH Abdul Chalim Mojokerto, 2023)
The leader is an authority figure in which case every gesture pattern and behavior can have an impact on the conditions and responses of subordinates and employees. The purpose of this study is to determine the impact and influence of the communication style and work motivation that the Principal of State Senior High School 57 Jakarta applies and has on the performance of the State Civil Apparatus (ASN) there. The method used in this research is a qualitative research method with the type of case study, the use of case studies because researchers can understand in depth the context, process, and complexity of the phenomenon being studied. The data collection techniques used are interviews, observation, and documentation. The results of the research found in the field show that the communication that exists between the Principal and all Teachers at SMAN 57 Jakarta is an effective communication style. Effective communication style allows the Principal to convey vision and goals, provide support to Teachers, promote collaboration, build trust, and solve problems together. In addition, based on the research conducted, it can be concluded that effective communication style is a manifestation of one of Horald-Lasswell's communication theories.